Probing the Clinical, Laboratory, and Sociodemographic Factors Associated with Malaria: A Case-Control Study - Ritesh Upadhyay; Annasaheb J. Dhumale; Chanchlesh Dehariya; Renu Waghmare; Amit Rangari (Journal of Pharmacy and Bioallied Sciences)
Background: The National Malaria Elimination Program (NMEP) has helped reduce the mortality from malaria in India, and there are alarmingly high mortality rates from anemia in certain geographical regions. Aim: To assess the clinical, laboratory, and sociodemographic factors associated with malaria from P. falciparum and P. vivax. Methods: This retrospective record-based clinical study subjects with malaria were further divided into P. vivax and P. falciparum cases. In all the cases, the clinical, laboratory, and sociodemographic factors were assessed. Data gathered were analyzed statistically. Results: During the study period, 222 cases of malaria were assessed where 22.52% (n = 50) and 74.48% (n = 172) cases were due to P. falciparum and P. vivax, respectively. Hepatomegaly was common in P. falciparum cases and splenomegaly in P. vivax cases. Thrombocytopenia was seen in 58.1% (n = 100) and 72% (n = 36) subjects with P. vivax and P. falciparum cases. No significant difference was seen in other laboratory parameters. Conclusions: Clinical, laboratory, and sociodemographic factors associated with malaria from P. falciparum and P. vivax have no statistically significant difference.